Trade performance of the less developed African countries - Fontoura, M. P.; Crespo, N. (Journal of Developing Areas, 2015)
Adopting a long term perspective, covering four decades, we evaluate the trade performance of a vast group of less developed African countries (LDAC). Besides some general trade indicators, we apply a constant market share analysis in order to decompose export performance (measured through the market share growth rate) into several components with specific economic interpretation. Our main conclusions are: (i) the sectoral specialization structure of LDAC exports has remained heavy in commodities but the composition of the basket of goods exported has changed considerably with a very strong concentration in crude oil (mainly in the last two decades), (ii) the geographical structure of exports has also changed, with an important increase of the relative importance of China and USA, (iii) LDAC not only show a negative competitiveness effect, but are also penalized by their sectoral and geographical specialization, and (iv) the most favorable evolution is observed in the most recent sub-period (2000-2007), but it is insufficient to reverse the negative trend of the previous decades.